ASEAN Way in Korean Peninsula Peacebuilding - Idham Badruzaman; Rafyoga Jehan Pratama Irsadanar (Department of International Relations, University of Mataram, 2020)
As stated by Johan Galtung, one fundamental principle in establishing peace is to involve the conflicting parties into a constructive dialogue. By this principle, ASEAN avoids isolative approach by welcoming Pyongyang in ASEAN Regional Forum (ARF) in 2000 and cultivating a trustworthy relationship afterwards. Driven by ASEAN Fundamental Principle in The Treaty of Amity and Cooperation (TAC) 1976, ARF appeared to be effective to maintain North Korea in negotiating table, as it also remains to be the only multilateral framework North Korea is in. This ASEAN soft diplomacy in peacebuilding also gains the positive support by Seoul as the engagement with ASEAN through its new southern policy intensifies. With ASEAN contribution as neighboring regional organization, many progresses of peacebuilding, such as Panmunjom Agreement, could be achieved. This paper analyses the role of ASEAN through its way of peacebuilding and soft diplomacy in mediating two Koreas and to help in maintaining peace in the region. This paper argues that ASEAN’s impartiality and traditional friendship among ASEAN members and two Koreas are the keys of ASEAN role in this regard.